Before the sun dies : the story of evolution - Gallant, Roy A. (London : Collier Macmillan, 1989)
Presents the theories, controversies, and latest scientific thinking on how the Solar System, the Earth, and the first biological organisms came to be and how the latter changed and adapted for survival. Includes a glossary of terms.
Includes index.
Bibliography: p. 177-179.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
8.9
Keywords: Evolution (Biology) -- Juvenile literature; Evolution; Evolution; Evolution